Factors affecting supply chain management in agribusiness a review of key concepts - Chojar, Anil K. (2009)
Commercial interest in supply chain management in agribusiness firms has increased due to greater urbanization and globalization. While product differentiation, improved quality, more cost-effective transport, and timely delivery have contributed to the development of supply chains from farm-gate to retail level, it is the consumer demand for variety, quality, and year-round availability that has provided the stimulus for the formation of these chains. Traditional agricultural and food businesses that focus only on price are unable to meet consumers' expectations. Individually, chain members lack the means to respond to consumers' demands. Understanding the concepts of supply chain management provides a means to manage the changes required in the system to efficiently respond to consumer needs, integrating and coordinating the efforts of all supply chain members. These changes include consolidating organizations at the farm, processors, and supermarket levels; organizing production to achieve economies of scale; and gaining market share and competitive strength to survive global competition. This paper highlights the importance of critical factors like mutual trust; leadership by one or two chain members; the use of information technology (IT) in input procurement, production planning, and market access; realignment of strategies to develop improved production methods to meet consumer preferences and food safety standards; and the intelligent use of market information to help small farmers to overcome production challenges and respond to the challenges of global markets.
Keywords: Suppy chain management; Farm gate information; Consumers